The Complexities of Race-Based Admissions in South African Universities - Sehoole, Chika; Adeyemo, Samuel; Phatlane, Rakgadi (International Higher Education, 2024)
Race has been a key feature of admissions in South African universities over the last 30 years. The admission policies coined around affirmative action have received conflicting criticisms in the academic literature. Some scholars argue that affirmative action policy promotes mainly the interests of Black students, challenges university autonomy, compromises quality, and recreates a new form of racial discrimination. Some of the views see admission of “Black” as compromising quality and lowering standards. This paper analyzes the different perspectives around race-based admission policies in South African universities and the outcomes of their implementation. It argues for a nuanced approach to admission policies beyond race, and advocates for other features of disadvantage to be considered beyond race.